Carbon- and crack-free growth of hexagonal boron nitride nanosheets and their uncommon stacking order. Issue 35 (25th July 2016) - Khan, Majharul Haque; Casillas, Gilberto; Mitchell, David R. G.; Liu, Hua Kun; Jiang, Lei; Huang, Zhenguo
Abstract : Large crystalline hexagonal boron nitride nanosheets are grown via chemical vapor deposition. Unusual stacking orders have been observed. This could inspire studies on the control of stacking order and order–property correlation. Abstract : The quality of hexagonal boron nitride nanosheets ( h -BNNS) is often associated with the most visible aspects such as lateral size and thickness. Less obvious factors such as sheet stacking order could also have a dramatic impact on the properties of BNNS and therefore its applications. The stacking order can be affected by contamination, cracks, and growth temperatures. In view of the significance of chemical-vapour-decomposition (CVD) assisted growth of BNNS, this paper reports on strategies to grow carbon- and crack-free BNNS by CVD and describes the stacking order of the resultant BNNS. Pretreatment of the most commonly used precursor, ammonia borane, is necessary to remove carbon contamination caused by residual hydrocarbons. Flattening the Cu and W substrates prior to growth and slow cooling around the Cu melting point effectively facilitate the uniform growth of h -BNNS, as a result of a minimal temperature gradient across the Cu substrate. Confining the growth inside alumina boats effectively minimizes etching of the nanosheet by silica nanoparticles originating from the commonly used quartz reactor tube. h -BNNS grown on solid Cu surfaces using this method adopt AB, ABA, AC′, and AC′B stacking orders, which are known to have higher energies than the most stable AA′ configuration. These findings identify a pathway for the fabrication of high-quality h -BNNS via CVD and should spur studies on stacking order-dependent properties of h -BNNS.